Natural disasters and market manipulation - Akter, Maimuna; Cumming, Douglas; Ji, Shan (Journal of Banking & Finance, 2023)
Natural disasters exacerbate swings in investor sentiment and information asymmetry. As such, we propose natural disasters enable more frequent and severe market manipulation. We test this proposition using the securities listed in the NYSE and NASDAQ, disaster data from the National Oceanic and Atmospheric Administration, and surveillance industry-provided manipulation data from SMARTS, Inc. The data indicate the frequency and severity of market manipulation increases during disaster periods. Community resilience, hazard mitigation programs, and operational location moderate the effect of natural disasters on manipulation. These effects are not mechanically driven by spikes in volatility in disaster-county months. These effects are more pronounced for certain industries, including agricultural, health, and manufacturing industries. Finally, these findings are robust to alternative proxies of manipulation and various model specifications that include but are not limited to using difference-in-differences analysis.